Pengaruh Penyuluhan Kesehatan Terhadap Pengetahuan Kesiapsiagaan Dalam Menghadapi Bencana Gempa Bumi Pada Mahasiswa STIKes Persada Husada Indonesia - Nuraeni, Dita Sri Wiji; Elwindra, Elwindra; Arimbi, Shella Olivia (Jurnal Persada Husada Indonesia, 2024)
Natural disasters are something unexpected and undesirable, so there is a need for education and knowledge regarding disaster management. This study aims to determine the effect of health education on knowledge of earthquake preparedness in level 1 students of STIKes PHI. This type of research uses Quasi Experiment with one group pretest – posttest design. Data collection was carried out at the PHI STIKes from June to July 2023. The population was all level 1 students at the PHI STIKes. Sampling purposive sampling as many as 44 people. The analysis used univariate analysis and bivariate analysis with t-test and chi-square test. The results of this study showed that the average preparedness knowledge of level 1 students at STIKes PHI in dealing with earthquake disasters before being given counseling was 34.02 and the average knowledge about level 1 student preparedness at STIKes PHI in dealing with earthquake disasters after being given counseling was 81.55. From the results of this study, the female gender has a higher level of knowledge than the male with a P-value of 0.021 (<0.05), which means that there is a significant influence between gender and knowledge level. The results of this research show that there is a significant influence between knowledge of earthquake preparedness in level 1 students of the PHI STIKes with a P-value of 0.000 (<0.05). It is hoped that institutions can increase the dissemination of information about earthquake disaster preparedness directly by disseminating education about earthquake disasters by increasing regular counseling and using training methods or earthquake preparedness simulations.